Determinants of Company Value in the Healthcare Sector Listed on the Indonesian Stock Exchange for the 2020–2024 Period - William Joash Emmanuel Hanson; Susanti Usman (Publikasi Indonesia, 2026)
Company value is an investor’s assessment of a company’s success. The value of a company is very important because it reflects the firm’s health, performance, and future prospects in the eyes of various parties, such as investors and management. This study aims to analyze the Investment Opportunity Set, earnings growth, company size, and profitability as determinants of Company Value, as well as to identify the variables that have the greatest influence on Company Value in healthcare sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This research employs a quantitative approach using secondary data obtained from the www.idx.com website and company websites over a five-year period (2020–2024). The total population of this study is 34 companies, and after the purposive sampling stage, a sample of 12 companies was obtained, yielding a total of 60 observations. The analysis method used in this study is panel data regression, processed using EViews version 13. The results indicate that the Investment Opportunity Set, earnings growth, and profitability are determinants of Company Value. Meanwhile, company size is not a determinant of Company Value, and the most influential variable is profitability in healthcare sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period